Reaction control method using carbon soot molecules and organometallic complexes in excited state - KAMIYA; TOSHIYUKI; HANAZATO; YOSHIO; ISODA; SATORU; IKEDA; AKIRA (1999)
A method and an apparatus for controlling reactions of a gas and a fluid that makes use of excellent reactivity of carbon soot molecules, metal porphyrin complexes and metal phthalocyanin complexes which are in an excited state has an arrangement that the carbon soot molecules, the metal porphyrin complexes and the metal phthalocyanin complexes which are excited by a physico-chemical method, such as light irradiation, and a gas containing oxygen are brought into contact with each other to generate active oxygen. Further, the gas containing the harmful substance and a fluid are brought into contact with each other so that direct reactions of the active oxygen and the excited molecules decompose the harmful substances.